A 3D Homochiral MOF [Cd2(d‐cam)3]2Hdma4dma for HPLC Chromatographic Enantioseparation. Issue 4 (22nd February 2016) - Zhang, Mei; Chen, Xinglian; Zhang, Junhui; Kong, Jiao; Yuan, Liming
Abstract: Up to now, some chiral metal‐organic frameworks (MOFs) have been reported for enantioseparation inliquid chromatography . Here we report a homochiral MOF, [Cd2(d‐cam)3]·2Hdma·4dma, used as a new chiral stationary phase for high‐performance liquid chromatographic enantioseparation. Nine racemates of alcohol, naphthol, ketone, and base compounds were used as analytes for evaluating the separation properties of the chiral MOF packed column. Moreover, some effects such as mobile phase composition, column temperature, and analytes mass for separations on this chiral column also were investigated. The relative standard deviations for the resolution values of run‐to‐run and column‐to‐column were less than 2.1% and 3.2%, respectively. The experimental results indicate that the homochiral MOF offered good recognition ability, which promotes the application of chiral MOFs use as stationary phase for enantioseparation. Chirality 28:340–346, 2016 . © 2016 Wiley Periodicals, Inc. Abstract :